2005
DOI: 10.1038/emm.2005.65
|View full text |Cite
|
Sign up to set email alerts
|

Receptor activator of NF-κB ligand enhances the activity of macrophages as antigen presenting cells

Abstract: Receptor activator of NFκB ligand (RANKL) is known as a key regulator of osteoclastogenesis. However, the fact that fibroblasts and periodontal ligament cells express RANKL in response to bacterial substances, suggests that RANKL may have evolved as a part of the immunity to infection. As RANKL increases the survival and activity of dendritic cells, it may have similar effects on macrophages. To address this issue, we studied the effect of RANKL on various functions of macrophages using mouse bone marrow deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 31 publications
0
26
1
2
Order By: Relevance
“…This axis has been implicated in the etiologies of diseases involving immune-associated bone loss, including rheumatoid arthritis, periodontitis, multiple myeloma, and even osteoporosis (Colucci et al, 2004;Wittrant et al, 2004;Takayanagi, 2005;Weitzmann and Pacifici, 2005;Walsh et al, 2006). RANKL enhances the survival and activity of dendritic cells and macrophages, acts as a chemotatic factor for monocytes (Breuil et al, 2003;Park et al, 2005) and regulates bone remodeling via the escalation of osteoclastogenesis and osteoclast activity (Wada et al, 2006 and references therein). OPG, a soluble decoy receptor for RANKL, regulates B cell maturation and the development of efficient antibody responses (Yun et al, 2001;Stolina et al, 2003), as well as the attenuation of bone resorption via its interfering action on RANKL (Wada et al, 2006 and references therein).…”
mentioning
confidence: 98%
“…This axis has been implicated in the etiologies of diseases involving immune-associated bone loss, including rheumatoid arthritis, periodontitis, multiple myeloma, and even osteoporosis (Colucci et al, 2004;Wittrant et al, 2004;Takayanagi, 2005;Weitzmann and Pacifici, 2005;Walsh et al, 2006). RANKL enhances the survival and activity of dendritic cells and macrophages, acts as a chemotatic factor for monocytes (Breuil et al, 2003;Park et al, 2005) and regulates bone remodeling via the escalation of osteoclastogenesis and osteoclast activity (Wada et al, 2006 and references therein). OPG, a soluble decoy receptor for RANKL, regulates B cell maturation and the development of efficient antibody responses (Yun et al, 2001;Stolina et al, 2003), as well as the attenuation of bone resorption via its interfering action on RANKL (Wada et al, 2006 and references therein).…”
mentioning
confidence: 98%
“…Osteoclast precursors were prepared as previously described with some modification (Park et al, 2005). Briefly, bone marrow cells were obtained from the tibia and femur of 5-week-old male ICR mice.…”
Section: Isolation Of Osteoclast Precursors and Osteoclastogenesismentioning
confidence: 99%
“…In addition to the pivotal role of RANKL in bone metabolism (Simonet et al, 1997), RANKL has also been shown to participate in various immune system functions as in the case of other members of the TNF ligand and TNF receptor superfamilies Park et al, 2005). RANKL was identified as a crucial factor in lymphocyte development and lymph node organogenesis (Anderson et al, 1997;Kong et al, 1999a, b).…”
Section: Introductionmentioning
confidence: 99%